Effect of dietary graded levels of dried lemon (citrus aurantifulia) pulp on performance, intestinal morphology, and humoral immunity in broiler chickens - Reihan Basir; Majid Toghyani (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Dried lemon pulp (DLP) is a by-product of fruit processing industry and is containing active antioxidants such as flavonoids, isoflavones, and flavones. Thus, current experiment was carried out to evaluate the effect of dietary graded levels of DLP on performance, intestinal morphology, and humoral immunity in broiler chickens. Methods Accordingly, a total of 280-day-old broiler chickens (Ross 308) were assigned to 4 treatments and 5 replicates of 14 chicks each. Dietary treatments included control (CON) with no additive as well as DLP1: 2.5, 5, and 7.5%; DLP2: 5, 7.5, and 10%; and DLP3: 7.5, 10, and 12% in starter, growing, and finisher phases, respectively. Subsequently, performance, intestinal morphology, and humoral immunity were evaluated throughout the experiment. Results Body weight of chickens decreased when using graded levels of DLP during different periods of the experiment as compared with CON (P.05). Also, daily weight gain was lower in those supplemented by 7.5% DLP than CON across finishing period (P.05). Therefore, feed conversion ratio of broilers was impaired when using graded levels of DLP across the entire production phase compared to the birds in CON group (P.05). Antibody titer against influenza disease virus and sheep red blood cells decreased when using DLP3 and DLP2, respectively (P.05). Jejunal crypt depth decreased in chickens fed on DLP3 compared with control. Conclusion Dietary graded levels of DLP modified intestinal segments while deteriorated growth performance of chickens. Furthermore, DLP3 decreased jejunal crypt depth. Thereby, the use of DLP particularly at high levels is not recommended.